MicroRNA Regulation of Brown Adipogenesis and Thermogenic Energy Expenditure - Shamsi, Farnaz; Zhang, Hongbin; Tseng, Yu-Hua (Frontiers in Endocrinology, 2017)
Obesity, diabetes and associated metabolic diseases have become global epidemic. Obesity results from excess accumulation of white fat, while brown and its related beige fat function to dissipate energy as heat, and thus counteracting obesity and its related metabolic disorders. Understanding the regulatory mechanisms for both white and brown adipogenesis provide new insights for prevention and treatment of these metabolic diseases. In addition to traditional gene transcription and translation, microRNA represents a new layer of regulatory mechanism in many biological processes, and have attracted a lot of research interests in exploring their roles in physiological and pathophysiological conditions. This review focuses on the recent advances of regulation of brown adipogenesis and energy metabolism by microRNAs, aiming to delineate the regulatory principles of microRNAs on this unique aspect of energy homeostasis.